Analisis Kemampuan Berpikir Kreatif Matematis Siswa Pada Materi Program Linear - Elkarisme, Yunice; Making, Samuel Rex M.; Lede, Yulius Keremata (Varied Knowledge Journal, 2023)
The purpose of this research was to determine the mathematical creative thinking skills of Class XI Sinar Buana Seminary High School students on Linear Programming material. The method used in this research is descriptive qualitative method. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results showed that students' mathematical creative thinking abilities were in the Medium category because seen from the level of success and student achievement, Sinar Buana Seminary High School students in solving problems on linear program material the achievement level of students with mathematical creative thinking abilities only a few students achieved indicator success.